2018
DOI: 10.1001/jamaoto.2018.0473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Patient-Specific, 3-Dimensionally Printed Endoscopic Sinus and Skull Base Surgical Model

Abstract: This study shows that high-resolution, 3D-printed sinus and skull base models can be generated with anatomical and haptic accuracy. This technology has the potential to be useful in surgical training and preoperative planning and as a supplemental or alternative simulation or training platform to cadaveric dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 18 publications
0
52
0
2
Order By: Relevance
“…Moving into the 3D-printing era, it is clear that such models-which can even be targeted on a case-by-case basis-can attain high anatomical accuracy [28]. Unfortunately, the more basic high-fidelity models do not [20] Animal simulators Sheep Head Rhinology Model Face and content [21] Predictive [22] Ovine Endoscopic Sinus model Content and construct [23] include soft tissue simulation as this requires more complex 3D printers.…”
Section: High-fidelity Ess Modelsmentioning
confidence: 99%
“…Moving into the 3D-printing era, it is clear that such models-which can even be targeted on a case-by-case basis-can attain high anatomical accuracy [28]. Unfortunately, the more basic high-fidelity models do not [20] Animal simulators Sheep Head Rhinology Model Face and content [21] Predictive [22] Ovine Endoscopic Sinus model Content and construct [23] include soft tissue simulation as this requires more complex 3D printers.…”
Section: High-fidelity Ess Modelsmentioning
confidence: 99%
“…Their printing methods and materials were compared to sheep femur for bony characteristics, which may not be a similar enough model to human temporal bone because sheep femur does not contain highly aerated bone segments like human petrous and mastoid temporal bone . 3D printed models also lack soft tissue, do not allow for simulation of bleeding during dissection, and like cadaveric temporal bones, the use of 3D printed models requires a specialized laboratory and significant clean‐up after use. The potential health risks associated with aerosolizing the printed material have yet to be determined.…”
Section: Applications Of Temporal Bone Simulationmentioning
confidence: 99%
“…The potential health risks associated with aerosolizing the printed material have yet to be determined. Additionally, an expert is still required to provide feedback during the learning process and the cost effectiveness of 3D printing models for each new simulation must still be evaluated …”
Section: Applications Of Temporal Bone Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies discussed the development of 3D-printed models which can be used in endoscopic skull base surgery, and some studies described 3D-printed physical simulators that are bene t to learning endoscopic techniques [9,15,[18][19][20][21]. However, few studies reported the application experience of 3D-printing technology used in skull base endoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%